TANGGUNG JAWAB PERUSAHAAN PENERBANGAN SEBAGAI PELAKU USAHA TERHADAP KEHILANGAN BARANG BAGASI PENUMPANG DITINJAU DARI UU NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Daniel J Napitupulu (2021)
Air Transportation is any activity using Aircraft to transport passengers, cargo and/or post for one or more trips from one airport to another or several airports. The problem in this research is about what are the legal protection barriers to air transport consumers in the event of loss of luggage on the plane. Another problem is what are the legal consequences of airlines as business actors for the loss of baggage. The research method used is normative research with a case approach and a statutory approach. Normative research is carried out by examining library materials or secondary data as the basis for research using qualitative analysis. The results of the study indicate that the barriers to legal protection for air transport consumers in the event of loss of baggage on the aircraft lie in the lengthy procedures and processes as contained in Law Number 1 of 2009 concerning Aviation and Regulation of the Minister of Transportation Number 77 of 2011 concerning Responsibilities of the Transport Carrier. Air, so they have to wait a long time and consumers as the party who loses luggage cannot get compensation at that time. Then the legal consequence of the airline company as a business actor for the loss of baggage is that the airline company must be responsible to consumers who suffer losses due to loss of baggage in accordance with Law Number 8 of 1999 concerning Consumer Protection by fulfilling consumer rights in the form of compensation in accordance with the amount regulated in Law Number 1 of 2009 concerning Aviation and Regulation of the Minister of Transportation Number 77 of 2011 concerning Responsibilities of Air Transport Carriers